The Importance of English for the Costa Rican Economy and Curriculum - Brand Fonseca, Kevin Armando (2022)
This case study analyzes the role of English in the Costa Rican economy and curriculum. It is grounded on a second language acquisition and learning framework related to socio-cultural and socio-cognitive theories, identity and agency, and motivation. The stakeholders that took part in the study were students, instructors, parents, employers, and heads of English teaching programs at the national level. The conclusions highlight the importance of the English language for the economic system. Also, identity and agency appear to be crucial factors to understand language learning as a complex process.